The Impact of Intercollegiate Athletics Financial Inequalities - Heather Lawrence (University of Kansas Libraries, 2013)
Inequality within intercollegiate athletics has roots as deep as the enterprise itself. From a macro perspective, financial inequality in intercollegiate athletics stems from free-market forces influencing intercollegiate athletics, specifically the National Collegiate Athletic Association (NCAA), television broadcasting, and the Bowl Championship Series (BCS). Because the NCAA operates on behalf of its member institutions, these inequalities trickle down to all conferences, universities, and athletic programs, to specific sports, and finally to student-athletes. The goal of this paper is to respond to Zimbalist (2013), add to the conversation about financial inequality in intercollegiate athletics, and describe how national inequalities translate into inequalities on campus. An analysis of the structure of intercollegiate athletics that perpetuates these inequalities is presented, Activity-Based Costing (ABC) is introduced, and practical ideas to assist in creating a more financially equitable model of intercollegiate athletics are presented.